2000
DOI: 10.1007/s003300051050
|View full text |Cite
|
Sign up to set email alerts
|

MR arthrography of the shoulder: comparison of low-field (0,2 T) vs high-field (1.5 T) imaging

Abstract: The objective of this study was to compare the image quality, sensitivity, specificity, and diagnostic accuracy of an open low-field MR system (0.2 T) with a standard high-field MR system (1.5 T) after arthrography of the shoulder. Thirty-eight patients either with suspected chronic instability (n = 12) or rotator cuff abnormalities (n = 26) were examined. Intra-articular injection of diluted Gd-DTPA was followed in randomized order either first by imaging on an open 0.2-T system or on a 1.5-T system. The imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…In musculoskeletal studies, low-field MRI may provide a cheaper alternative to the more expensive mid-and high-field MR systems [13,14,15]. The results of our study show that Vsm (E-MRI) was significantly correlated with and did not differ significantly from Vsm (high-field MRI) independently of Gd.…”
Section: Discussionsupporting
confidence: 36%
“…In musculoskeletal studies, low-field MRI may provide a cheaper alternative to the more expensive mid-and high-field MR systems [13,14,15]. The results of our study show that Vsm (E-MRI) was significantly correlated with and did not differ significantly from Vsm (high-field MRI) independently of Gd.…”
Section: Discussionsupporting
confidence: 36%
“…When compared with high-field imaging, the same working group found that overall image quality was rated significantly lower with low-field imaging [20]. Again, there was excellent or substantial agreement between two readers with respect to image quality and motion artifacts for both systems (κ=0.89 and 0.87 for highfield imaging, κ=0.79 and 0.67 for low-field imaging, respectively).…”
Section: Image Qualitymentioning
confidence: 81%
“…Again, this may be related to the particular surgical technique, arthroscopic criteria, or patient population associated with this particular site. Several studies have reported that the use of intraarticular contrast improves the diagnostic capabilities of MR imaging for the glenoid labrum when compared to conventional MR imaging (7,15,16,(32)(33)(34)(35)(36). Therefore, the possibility exists that MR arthrography performed with the extremity MR system may result in increased sensitivity and specificity for tears of the glenoid labrum.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the possibility exists that MR arthrography performed with the extremity MR system may result in increased sensitivity and specificity for tears of the glenoid labrum. In fact, Loew et al (35) reported that, when using MR arthrography, low-field (0.2 Tesla) MR imaging compared favorably to high-field MR imaging in the detection of major abnormalities of the glenohumeral joint. For labral pathologies, the sensitivity and specificity were 100 and 93%, respectively (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation